Evaluation of Financial Statements in Assessing the Financial Performance of the Local Government of South Labuhanbatu Regency - Purba, Sahala; Marpaung, Catherine Audry Rebecca; Sinaga, Deda Sasmita; Ginting, Emisa Clara Br; Sirait, Tessa Anggraini (Fakultas Ekonomi Prodi Akuntansi, 2024)
South Labuhanbatu Regency financial management is limited by established regulations, such as South Labuhanbatu Regent Regulation Number 66 of 2018 concerning Management of Information and Documentation Services within the South Labuhanbatu Regency Government. The South Labuhanbatu Regency Government carries out observations and research in carrying out research, as was carried out in research using a methodology published in 2018This study aims to evaluate the financial performance of the local government of South Labuhanbatu Regency based on the following factors: (1) Regional Autonomy Level Ratio (2) Regional Financial Dependence Ratio (3) Fiscal Decentralization Rate Ratio (4) Regional Original Revenue Effectiveness Ratio (5) Regional Original Revenue Efficiency Ratio (6) Regional Fiscal Management Effectiveness Ratio (7) Regional Tax Management Efficiency Ratio (8) Contribution Rate Ratio of Regional Owned Enterprises. The data is analyzed based on the theories of previous experts, then explained in detail for decision making on the financial performance of local governments. Based on the research conducted, the results show the regional financial performance of South Labuhanbatu Regency from 2013 to 2022 as follows: (1) The Regional Autonomy Level Ratio shows a very low level, with an average value of 6.98%, (2) the Regional Financial Dependence Ratio shows a high category, with an average value of 90.75%, (3) The Fiscal Decentralization Rate Ratio shows a very low level, with an average of 6.21%, (4) the Regional Original Revenue Effectiveness Ratio shows the less effective category with an average of 7.87%, (5) the Regional Original Revenue Efficiency Ratio shows the very efficient category with an average of 92.93%, (6) the Regional Fiscal Management Effectiveness Ratio shows the fairly effective category with an average of 97.74%, (7) the Regional Tax Management Efficiency Ratio shows the efficient category with an average of 19.37%, (8) The ratio of the degree of contribution of Regional-Owned Enterprises shows a contribution of 2.87%. So in this case the central government has failed in developing BUMD in South Labuhanbatu district. From the results of this analysis, it can be concluded that overall the development of South Labuhanbatu Regency carried out by the central government has been successfully implemented, this can be seen from the analysis of regional government financial reports which are reviewed from 8 measurement proportions, South Labuhanbatu Regency which has 4 measurement proportions that have been successful , while the proportion of 4 measurements that were unsuccessful, it can be seen that the proportion of measurements that were successful and those that were unsuccessful were the same. The suggestion in this analysis is that the South Labuhanbatu regional government can optimize human resources and natural resources as well as pay attention to infrastructure development and also increase the number of years of observation.